Opportunities for forage production from degraded lands - Ghosh, P. K.; Kumar, Sunil; Ram, S. N. (Indian Farming, 2015)
In animal husbandry grazing plays an importent role in the rural economy of an agarian country. The grazing activity of animals is dependent upon the availability of the grazing resources. The degraded lands in India, provide an alternative land use option for silvihortipasture. This option of alternative land use system, not only checks soil erosion but also improves the productivity of land and migitages the requirement of fodder, fuel, fruit and timber. The results on production of biomass through various silvi/horti-pasture systems on different degraded lands show that they are very much beneficial for getting higher biomass production from the same land on sustainable basis.